The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/plants10122665
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Small RNAs Differentially Expressed in Apple Buds Reveals a Potential Role of the Mir159-MYB Regulatory Module during Dormancy

Abstract: Winter dormancy is an adaptative mechanism that temperate and boreal trees have developed to protect their meristems against low temperatures. In apple trees (Malus domestica), cold temperatures induce bud dormancy at the end of summer/beginning of the fall. Apple buds stay dormant during winter until they are exposed to a period of cold, after which they can resume growth (budbreak) and initiate flowering in response to warmer temperatures in spring. It is well-known that small RNAs modulate temperature respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
1
9
0
1
Order By: Relevance
“…In our previous study, two SVP homologous genes ( CpSVP1 and CpSVP2 ) were identified from the transcriptome of wintersweet floral buds and considered as candidate genes for regulating floral bud dormancy [ 41 ]. However, miRNA6390 was not identified in all of the sRNA libraries in this study, and miRNAs targeting CpSVP1 or CpSVP2 were not found, which is similar to the results reported in Japanese pear, peach, and apple [ 37 , 39 , 59 ]. The reason for such differences may be different species, indicating that the regulatory roles of miRNAs in plant bud dormancy release may vary among species or even cultivars.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our previous study, two SVP homologous genes ( CpSVP1 and CpSVP2 ) were identified from the transcriptome of wintersweet floral buds and considered as candidate genes for regulating floral bud dormancy [ 41 ]. However, miRNA6390 was not identified in all of the sRNA libraries in this study, and miRNAs targeting CpSVP1 or CpSVP2 were not found, which is similar to the results reported in Japanese pear, peach, and apple [ 37 , 39 , 59 ]. The reason for such differences may be different species, indicating that the regulatory roles of miRNAs in plant bud dormancy release may vary among species or even cultivars.…”
Section: Discussionsupporting
confidence: 88%
“…By contrast, 21-nt sRNAs are most abundant in apple ( Malus domestica cv.) and masson pine ( Pinus massoniana ) [ 11 , 37 ]. These results suggest that sRNA transcripts are complex and vary significantly in different plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In A. nanus , 53 lncRNAs were identified as miRNA precursors, and the corresponding miRNAs belonged to 20 miRNA families, including MIR156, MIR159, MIR167, MIR172, MIR390, MIR393, MIR396, and MIR398. It was reported that cold-responsive miRNAs, including miR156 [ 42 ], miR159 [ 43 ], miR167 [ 44 ], miR172 [ 45 ], miR390 [ 46 ], miR393 [ 47 ], miR396 [ 48 ], and miR398 [ 49 ], played critical regulatory roles in the response of plants to cold stress by negatively regulating their targets. Long non-coding RNAs can also act on protein-coding genes that are targeted by miRNAs by competitively binding to the miRNAs, thereby forming lncRNA–miRNA–mRNA regulatory modules [ 50 ].…”
Section: Discussionmentioning
confidence: 99%